2009
DOI: 10.1302/0301-620x.91b9.21750
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular revision with impacted morsellised cancellous bone grafting and a cemented acetabular component

Abstract: We present an update of the clinical and radiological results of 62 consecutive acetabular revisions using impacted morsellised cancellous bone grafts and a cemented acetabular component in 58 patients, at a mean follow-up of 22.2 years (20 to 25). The Kaplan-Meier survivorship for the acetabular component with revision for any reason as the endpoint was 75% at 20 years (95% confidence interval (CI) 62 to 88) when 16 hips were at risk. Excluding two revisions for septic loosening at three and six years, the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 24 publications
3
86
0
4
Order By: Relevance
“…Last, we also lacked biopsies and autopsy retrieval of acetabula reconstructed with this technique to confirm the bone graft remodeling and new bone formation. Like in other series [12,32], we observed that the use of IBG and a cemented cup in acetabular revision surgery is a durable option for large defects. Postoperative cup position improved in this series, even for hips with 3B, findings that may promote low rates for rerevision, which depends on achieving adequate fixation of the new implant, restoring the anatomic center of rotation of the hip, and restoring bone stock loss [39].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Last, we also lacked biopsies and autopsy retrieval of acetabula reconstructed with this technique to confirm the bone graft remodeling and new bone formation. Like in other series [12,32], we observed that the use of IBG and a cemented cup in acetabular revision surgery is a durable option for large defects. Postoperative cup position improved in this series, even for hips with 3B, findings that may promote low rates for rerevision, which depends on achieving adequate fixation of the new implant, restoring the anatomic center of rotation of the hip, and restoring bone stock loss [39].…”
Section: Discussionsupporting
confidence: 83%
“…The impaction bone grafting (IBG) technique was introduced for use in the acetabulum by Slooff et al [35] and has proven to be effective in revision surgery. Different series have confirmed excellent results using this technique [10,30,32,33] and bone graft incorporation has been reported in histologic and positron emission tomography studies [2,4,28,31,34,37]. In a goat model of impacted allograft, Schimmel et al [28] showed complete incorporation of the allograft by 48 weeks.…”
Section: Introductionmentioning
confidence: 75%
“…Jumbo cups have been associated with favorable survivorship of 92% to 96% at 14 to 16 years [19,27] where adequate support can be obtained. Acetabular impaction grafting has shown promising results with 87% survivorship for aseptic loosening at 20 years and 75% for any cause of failure [30]; however, it is technically demanding, time-consuming, and may be associated with higher failure rates in massive bone loss [6]. Combining the technique with trabecular metal augments to support large areas of graft offers promising early results [15].…”
Section: Discussionmentioning
confidence: 99%
“…Impaction bone allografting was used for reconstruction in most of the revised cups (10 of 12 cups). Like in other series [45], the impression at rerevision was that the original bone grafting had been incorporated, and a new bone impacting grafting was performed because part of the existing graft looked viable and well healed to the host-bone. Unfortunately, we did not make core biopsies in any case to confirm whether the bone was viable on the periphery of the graft.…”
Section: Discussionmentioning
confidence: 99%
“…Impacted morselized bone allograft and cement in the acetabulum have been used in revision surgery [13,18,45,48] and bone graft incorporation has been reported in histologic studies [5,41,44,47]. In a goat model of impacted allografts, Schimmel et al [41] showed complete incorporation of the allograft by 48 weeks.…”
Section: Introductionmentioning
confidence: 99%